Genetic variation in MdNAC72 regulates MdNAC18 to control flesh firmness/crispness in apple fruit - Guo Wen; Zhongyi Xie; Jingmiao Huang; Hao Fu; Limin Lin (Postharvest Biology and Technology, 2026)

Programmable co-assembly of plasmonic nanostructures enabling self-calibrated SERS detection of nitrite - Pengxiang Wang; Kaiqiang Wang; Zhihui Wu; Xujian Qiu; Limin Cao; Jianxin Sui; Xiudan Wang; Hong Lin (Analytica Chimica Acta, 2026)

Functional Validation of the Phase I–II–III Detoxification Pathway in Azumapecten farreri using Optimized RNA Interference Technology - Limin Lu; Guanchao Zheng; Yichen Lin; Chenfan Dong; Jixing Peng; Haiyan Wu; Zhijun Tan (Marine Biotechnology, 2026)

Single-enzyme level inorganic–organic engineering enables long-term stabilization of paper-based enzyme biosensors for hypoxanthine detection in food samples - Fengyi Li; Hong Lin; Chuan Zhang; Jing Li; Limin Cao; Jianxin Sui; Kaiqiang Wang; Lusheng Xin; Xiaokun Wang; Xiudan Wang (Chemical Engineering Journal, 2026)

Change detection-based machine learning for earthquake-triggered landslide identification in complex mountain landscapes - Lin Wang; Limin Zhang; Feng Cheng; Xiwei Fan; Shuang Li (Geomorphology, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Hydroclimatic Regime Shift Weakens Snowmelt Regulation of Summer Heat Extremes in Northern China - Jing Lin; Baolin Xue; Junping Wang; Xianhong Xie; Guoqiang Wang; Limin Duan (International Journal of Climatology, 2026)
Changes in precipitation phase and seasonal water supply can modify land‐surface moisture memory, but their implications for summer heat extremes remain insufficiently understood in midlatitude dryland transition zones. Northern China has experienced substantial hydroclimatic changes in recent decades, yet it remains unclear whether these changes have altered the efficiency with which spring snowmelt regulates subsequent summer heat extremes. Using daily observations from 348 meteorological stations during 1980–2019, we examined long‐term changes in precipitation phase and seasonal hydroclimatic conditions and assessed how effective cumulative spring snowmelt ( M AM ) is linked to summer heat extremes. We identified a hydroclimatic transition around 2000, with northern China shifting from a ‘warming‐without‐wetting’ to a ‘warming‐wetting’ regime, mainly associated with increased summer rainfall. This transition was spatially heterogeneous: northwestern China experienced persistent wetting with increases in both snowfall and rainfall, northeastern China became wetter primarily because of increased rainfall, whereas North China retained a warming‐drying tendency. Against this background, response analysis showed that greater M AM was generally accompanied by fewer and weaker summer heat events. The regulatory association of M AM was consistently stronger for T max than for N hot . Pathway analysis further suggested that antecedent upper‐root‐zone soil moisture and surface energy partitioning mediated the snowmelt–heat linkage, with additional modulation by summer rainfall. After 2000, mean effective cumulative spring snowmelt decreased, soil moisture and latent heat flux decreased, while sensible heat flux and summer heat metrics increased. These changes indicate a weakened M AM ‐related regulation of T max and a reduced efficiency of snowmelt‐derived moisture buffering under the post‐2000 hydroclimatic background. These results suggest that recent hydroclimatic change in northern China has altered not only seasonal water availability but also the land‐surface regulation of summer heat extremes, with implications for understanding how climate warming reshapes regional water–heat interactions and amplifies heat risk.

Dual-modulated anthocyanin-based freshness indicators with improved stability using 2,5-dihydroxybenzoic acid and UiO-66-NH2 - Hao Fang; Limin Cao; Jianxin Sui; Xiudan Wang; Hong Lin; Kaiqiang Wang; Jinjie Li (Food Chemistry, 2026)

A comprehensive review of molecular and biological factors associated with cell death patterns in fish and potential effects on postmortem flesh quality - Xiudan Wang; Hong Lin; Kaiqiang Wang; Limin Cao; Lusheng Xin; Jianxin Sui (Food Chemistry, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

Molting disruption in fall armyworm by an ankyrin-based Bracovirus factor from the parasitoid wasp Microplitis prodeniae Rao and Chandry - Yaru Wang; Farman Ullah; Liuying Lin; Xiangyun Cai; Ge Gao; Limin Chen; Zhiming Chen; Raul Narciso C. Guedes; Yaobin Lu; Jinda Wang; Youming Hou (Journal of Pest Science, 2026)

Turbulent flame structures of premixed prevaporized n-heptane/air in thin and broken reaction zone regimes - Wenjun Lin; Hongchao Dai; Xiao Cai; Limin Su; Jinhua Wang; Zuohua Huang (Fuel, 2026)

A novel compound nutrition powder ameliorates scopolamine-induced cognitive impairment via activating the PKA/CREB/BDNF signaling pathway and restoring cholinergic function - Xiaomeng Xu; Zihan Yuan; Enhui Ma; Limin Zhong; Dong Chen; Songyi Lin (Food Bioscience, 2026)

Unannotated noncoding transcripts as a source of intratumor heterogeneity in malignant cell states - Xiaolan Zhou; Limin Lin; Yu Chen; Guangrui Yang; Ting Ni; Zhaozhao Zhao (Science China Life Sciences, 2026)

Nitrogen-removal collapse and recovery: Integrative meta-omics insights into seasonal microbiome dynamics and cold-adaptive mechanisms in a full-scale activated sludge system - Limin Lin; Xinyu Zhu; Xiaoxing Lin; Ze Zhao; Hui Wang; Huizhen Yan; Feng Ju (Water Research, 2026)

Sorbitol-enhanced butyric acid production in mixed-culture anaerobic fermentation of potato peel waste - Yu Lu; Ke Zheng; Fei Zhao; Lin Ding; Limin Zheng; Jiying Zhu (Journal of Environmental Management, 2026)

Trends in global trade-embodied employment: analysis on economies, sectors, and benefit - Zekun Lin; Jianyi Lin; Mingliang Liu; Limin Kou; Weijiao Li; Sheng Pan (Journal of Industrial Ecology, 2026)

Modular indirect labeling strategy enables universal and cost-efficient SERS immunochromatography for trace carbofuran detection - Junlin Chen; Keli Wang; Hong Lin; Limin Cao; Jianxin Sui; Xiudan Wang; Kaiqiang Wang (Food Chemistry, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Human-induced changes in fluvial regimes for organic carbon supply and burial off the Yellow River Estuary - Li Jiang; Limin Hu; Naishuang Bi; Jinya Xu; Jun Ye; Lin Liu; Fudong Lin; Weini Chong; Jiazong Du; Xiao Wu; Houjie Wang (Water Research, 2026)

Advancing bidirectional hydrogen spillover in heterostructure catalysts for electrocatalytic antimony removal and recovery from wastewater - Yuhao Lin; Yanling Wu; Xiaojia Jiang; Qi Wang; Yanbiao Liu; Limin Jin (Journal of Hazardous Materials, 2026)

The regulatory mechanism of soybean peptides on flavor and quality of infant formula nutrition powder during storage:Novel insights into lipid and protein oxidation - Liu Dong; Yuanhong Gao; Limin Zhong; Songyi Lin (Food Bioscience, 2026)

Lactobacillus johnsonii JJB3 Ameliorates Oxidative Stress-Induced Intestinal Injury and Mitochondrial Damage by Promoting BNIP3L-Mediated Mitophagy - Xingmei Liu; Jinge Xin; Ning Sun; Yuhua Qin; Haonan Huang; Benhao Chen; Lixiao Duan; Yanxi Zhou; Dandan Wang; Bo Jing; Yan Zeng; Dong Zeng; et al. (Probiotics and Antimicrobial Proteins, 2026)

Tracking mitigation and expression patterns of the antibiotic resistome during full-scale livestock wastewater treatment: Comparison between summer and winter conditions - Xinyu Zhu; Limin Lin; Feng Ju (Water Research, 2025)

Optimal financial portfolio selection using a metaheuristic approach with multiple strategies - Limin Wang; Guosen Lin; Qijun Zhang; Muhammet Deveci; Seifedine Kadry; Mingyang Li (Swarm and Evolutionary Computation, 2025)

Recent advances in SERS hotspot regulatory strategies and their applications in food safety detection - Pengxiang Wang; Hong Lin; Limin Cao; Jianxin Sui; Xiudan Wang; Kaiqiang Wang (Food Chemistry, 2025)

Boosting visible-light photocatalytic antibiotic degradation with g-C3N4 nanosheet-functionalized UiO-66-NH2(Hf) heterojunctions - Ting Liao; Zhiyong Lin; Yicheng Huang; Wentao Li; Kaixin Li; Zhihui Huang; Xinrui Zhao; Limin Geng (Chemical Engineering Journal, 2025)

Stellaris Somnia-inspired interlaced gold nanoarray as a novel hotspot-optimized SERS platform for food hazards detection - Pengxiang Wang; Hong Lin; Limin Cao; Jianxin Sui; Xiudan Wang; Kaiqiang Wang (Journal of Hazardous Materials, 2025)

Deep learning algorithm-assisted non-destructive detection of TBARS values of salmon flesh using multi-modal molecular spectra fusion - Minqiang Guo; Hong Lin; Hua Feng; Limin Cao; Jianxin Sui; Xiudan Wang; Kaiqiang Wang (Food Chemistry, 2025)

Elucidation of the memory-improving mechanism of Antarctic krill peptide FPF targeting the hippocampus and protein regulation based on proteomics technology - Jingqi Yang; Limin Zhong; Dong Chen; Beiwei Zhu; Songyi Lin (Food Bioscience, 2025)

Construction of aliphatic channels in covalent organic framework for efficient separation of benzene and cyclohexane - Borui Cai; Xiaozeng Miao; Limin Duan; Xi Yang; Wenhao Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2025)

Unveiling anthocyanins structural basis with multiplexed colorimetric and SERS responses for smart monitoring of seafood freshness - Huiwen Liu; Limin Cao; Jianxin Sui; Hong Lin; Xiudan Wang; Kaiqiang Wang (Food Chemistry, 2025)

Dual-ion charge storage mechanism in polypyrrole cathodes for zinc-ion hybrid capacitors - Jiali Zhang; Tao Xue; Yongbiao Mu; Hongjie Li; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Unraveling the protein corona formation during the surface-enhanced Raman spectroscopy detection of malachite green in fish - Junlin Chen; Hong Lin; Limin Cao; Jianxin Sui; Xiudan Wang; Kaiqiang Wang (Food Chemistry, 2025)

Selective ·OH generation in Fenton-like reaction by dual sulfur coordination of iron organic frameworks - Limin Duan; Huihao Jiang; Borui Cai; Jiali Wang; Wenhao Wu; Daohui Lin; Kun Yang (Water Research, 2025)

Dynamic analysis of long-span bridges with vibration control systems: A novel reduced-order model and comparative study - Zhanhang Liu; Limin Sun; Lin Chen; Ashraf El Damatty (Engineering Structures, 2025)

Quasi-Solid-State Electrolytes: Bridging the gap between solid and liquid electrolytes for zinc-ion batteries - Tao Xue; Jinpeng Guan; Yongbiao Mu; Meisheng Han; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

From non-affinity to high-affinity: Rapid preparation of nanobodies utilizing high-precision alphafold and structural-interaction analysis for detection of enrofloxacin in marine fish - Guoqiang Li; Chang Liu; Shuo Qiu; Lin Wei; Limin Cao; Kaiqiang Wang; Xiudan Wang; Hong Lin; Jianxin Sui (Journal of Hazardous Materials, 2025)

Outliers removal based on geometric coherence constraints in remote sensing image matching - Leilei Jia; Lin Shi; Dongdong Shi; Limin Liu (International Journal of Remote Sensing, 2025)

Dynamic response reduction of floating offshore renewable energy applications with a high-damping mooring system - Daixin Yang; Satish Nagarajaiah; Lin Chen; Limin Sun; Biswajit Basu (Ocean Engineering, 2025)

Dynamic response of vegetation to meteorological drought and driving mechanisms in Mongolian Plateau - Shenghang Gao; Shengzhi Huang; Vijay P. Singh; Xiaoya Deng; Limin Duan; Guoyong Leng; Wenwen Guo; Yifei Li; Lin Zhang; Zhiming Han; Qiang Huang (Journal of Hydrology, 2025)

Selective degradation of KOH activated biochar adsorbed 4-chlorophenol with fulvic acid by peroxydisulfate - Min Hu; Laigang Hu; Xiaozeng Miao; Limin Duan; Ling Jiang; Hongxia Zhu; Wenhao Wu; Daohui Lin; Kun Yang (Journal of Environmental Chemical Engineering, 2025)

Temporal trend of organic carbon in the East Siberian Arctic shelf sediments and its relation to the recent climate forcing - Jialong Luo; Li Jiang; Limin Hu; Zenghui Yu; Weini Chong; Fudong Lin; Fenghua Su; Yanguang Liu; Kirill Aksentov; Alexander Bosin; Anatolii Astakhov; Xuefa Shi (Acta Oceanologica Sinica, 2025)

A prominent oxygenation event in the late Mesoproterozoic broke the calm of the second half of the “Boring Billion” - Lin Meng; Xiaoying Shi; Limin Zhou; Jie Li; Wei Liu; Baozeng Xie; Longfei Sun; Dongtao Xu; Lei Xu; Xinqiang Wang; Dongjie Tang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Insights into the recognition mechanism of shark-derived single-domain antibodies with high affinity and specificity targeting fluoroquinolones - Chang Liu; Guoqiang Li; Yuan Chen; Hong Lin; Limin Cao; Kaiqiang Wang; Xiudan Wang; Martin F. Flajnik; Jianxin Sui (Marine Life Science & Technology, 2025)
In this study, we investigated the molecular recognition mechanisms of shark-derived single-domain antibodies (ssdAbs) targeting fluoroquinolones using an integrated approach that combines in silico homologous modeling, molecular dynamics simulations, molecular docking, and alanine scanning mutagenesis. Three ssdAbs—2E6, 1N9, and 1O17—specific to enrofloxacin, norfloxacin, and ofloxacin, respectively, were selected based on previous work. Through AlphaFold2 and GalaxyWEB, the protein structures of these ssdAbs were predicted and optimized, followed by molecular dynamics simulations to emulate realistic protein behavior in a solvent environment. Molecular docking, alanine scanning mutagenesis, and subsequent verifications identified 30N and 93W of 2E6; 30N, 89R, 98Y, and 99D of 1N9; 100W and 101R of 1O17, all located within the complementarity determining region 3 loop, as critical for antigen binding. These residues primarily interact with their targets through hydrogen bonds, salt bridges, π–π stackings, and cation–π interactions. This study revealed, for the first time, the binding mechanism of ssdAbs to fluoroquinolones from a theoretical perspective, emphasizing the importance of aromatic and polar residues in recognizing characteristic epitopes, such as the carboxyl group at the C3 position and the 1-piperazinyl group at the C7 position. Our findings provide valuable insights for the rational design and enhancement of ssdAbs for detecting small molecule hazards in aquaculture.

Novel solid-phase extraction promotes simultaneous colloidal gold immunochromatographic assay of malachite green, leuco-malachite green, chloramphenicol, and semi-carbazone metabolites in aquatic products - He Ziyang; Zhang Shaoen; Chen Qingzhou; Lin Hong; Sui Jianxin; Wang Kaiqiang; Wang Huiying; Cao Limin (Food Chemistry, 2025)

Unveiling the regulatory mechanism of pulsed electric field modified instant soy milk powder: Exploring allergenicity, conformation, and epitopes - Jie Ding; Yaru Li; Limin Zhong; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Chemistry, 2025)

Exploring critical quality indicators and developing a non-destructive detection method using near-infrared spectroscopy for sea bass (Lateolabrax japonicus) quality evaluation - Ting Ma; Hong Lin; Limin Cao; Jianxin Sui; Qing Wang; Kaiqiang Wang (Food Chemistry, 2025)

Volatile organic compounds at a highland forest site in the southeast of the Tibetan Plateau: Source apportionment and reactivity contributions - Shuzheng Guo; Chunxiang Ye; Weili Lin; Yi Chen; Limin Zeng; Xuena Yu; Jinhui Cui; Chong Zhang (Environmental Pollution, 2025)

In vitro and in vivo investigation of the inhibitory effects of Sinoporphyrin sodium-mediated Sonodynamic therapy on human oral squamous cell carcinoma - Guogang Dong; Limin Jia; Shuhua Gao; Monan Lin; Ruilin Wang; Fuyu Yang; Juanjuan Ruan; Yanhong Lv (Journal of Photochemistry and Photobiology B: Biology, 2024)

Preparation and characterization of fish-derived protein gel as a potential dysphagia food: Co-mingling effects of inulin and konjac glucomannan mixtures - Qian Chen; Yanyan Wu; Limin Cao; Yongqiang Zhao; Huan Xiang; Hong Lin; Yueqi Wang (Food Chemistry, 2024)

A loss-of-function mutation in OsTZF5 confers sensitivity to low temperature and effects the growth and development in rice - Limin Wang; Ru Wang; Xin Cai; Huiqi Zheng; Yuxing Huang; Yuechen Li; Mingyue Cui; Mingli Lin; Huiwu Tang (Plant Molecular Biology, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

An optically responsive cancer vaccine for inducing robust anti-tumor immunity by apoptotic body carrying nanoadjuvants - Limin Jin; Shupei Sheng; Yan Zhang; Weiting Sun; Lin Mei; Dunwan Zhu; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Sedimentary record of water-sediment regulation and channel shifts in the Yellow River (Huanghe) Delta - Shuqing Qiao; Xuefa Shi; Jianbu Wang; Lin Zhou; Yonggui Yu; Naishuang Bi; Limin Hu; Gang Yang; Zhengquan Yao (Marine Geology, 2024)

Data fusion of near-infrared and Raman spectroscopy: An innovative tool for non-destructive prediction of the TVB-N content of salmon samples - Minqiang Guo; Hong Lin; Kaiqiang Wang; Limin Cao; Jianxin Sui (Food Research International, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

The construction of ofloxacin detection in fish matrix based on a shark-derived single-domain antibody - Chang Liu; Yuan Chen; Hong Lin; Limin Cao; Kaiqiang Wang; Xiudan Wang; Jianxin Sui (Analytica Chimica Acta, 2024)

Bimetallic Fe/Ni metal organic framework-based hypoxanthine biosensor for early monitoring of freshness changes of aquatic products - Zhuoran Li; Limin Cao; Jianxin Sui; Lei Wang; Hong Lin; Kaiqiang Wang (Food Chemistry, 2024)

Seafood waste derived carbon nanomaterials for removal and detection of food safety hazards - Ziyang He; Hong Lin; Jianxin Sui; Kaiqiang Wang; Huiying Wang; Limin Cao (Science of The Total Environment, 2024)

Improving the detection accuracy of the dual SERS aptasensor system with uncontrollable SERS “hot spot” using machine learning tools - Junlin Chen; Hong Lin; Minqiang Guo; Limin Cao; Jianxin Sui; Kaiqiang Wang (Analytica Chimica Acta, 2024)

Predicting temporal and spatial 4-D ocean temperature using satellite data based on a novel deep learning model - Yuliang Liu; Lin Zhang; Wei Hao; Lu Zhang; Limin Huang (Ocean Modelling, 2024)

Weather regimes associated with summer precipitation over the southeast Tibetan Plateau and the relationship with ENSO - Qixu Li; Zhiqiang Lin; Shunwu Zhou; Limin Yang; Jun Du; Zhenbo Zhou (International Journal of Climatology, 2024)
The Tibetan Plateau (TP), known as the “Asian water tower,” provides freshwater resources for hundreds of millions of people in Asia. Most of the Asian rivers, such as the Yangtze, the Jinsha, the Salween and the Brahmaputra, are generated from southeastern part of the TP (SETP). In order to explore the influences of atmospheric circulation on the precipitation over the SETP, self‐organizing mapping (SOM) was utilized to identify the weather regimes (WRs) and related precipitation over the SETP and its surrounding areas. The daily scale of large‐scale circulation via ERA5 were classified into nine WRs by the SOM. There are two favourable regimes (rainy WRs) and three adverse ones (rainless WRs) for the SETP precipitation among these WRs, respectively. Furthermore, water vapour transport of the WRs and the relevant effects of ENSO are investigated. The droughts and floods of SETP are determined by the interannual variations of occurred frequency of the WRs. In particular, the SETP is flooded in the years with frequent occurrence of the rainy WRs and vice versa. The occurrence of WRs is closely related to the phase state of ENSO. The 9th WR (SOM9) and the 4th WR (SOM4) are separately occurred more frequently in the El Niño and the La Niña years. Regulation of ENSO on the SETP precipitation are effective through its influences on the state of atmospheric circulation, that is, frequency of various WRs. It implies that the occurred frequency of WRs is modulated by the climate systems and results in the interannual variations of precipitation over the SETP.

Competitive enrichment of comammox Nitrospira in floccular sludge - Jiaying Hou; Ying Zhu; Jinzhong Liu; Limin Lin; Min Zheng; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Water Research, 2024)

Integrated transcriptomic and proteomic analyses uncover the early response mechanisms of Catharanthus roseus under ultraviolet-B radiation - Zhuoheng Zhong; Mengmin Wu; Tiancai Yang; Xiaoyue Nan; Shuyao Zhang; Lin Zhang; Limin Jin (Journal of Photochemistry and Photobiology B: Biology, 2024)

Distribution and sources of polycyclic aromatic hydrocarbons in surface sediments of the East China marginal seas: Significance of the terrestrial input and shelf mud deposition - Qi Shen; Huimin Yu; Yibo Cao; Zhigang Guo; Limin Hu; Lian Duan; Xueshi Sun; Tian Lin (Marine Pollution Bulletin, 2024)

Ultralow-Concentration (0.1M) Electrolyte for stable bulk alloy (Sn, Bi) anode in Sodium-ion battery via Regulating Anions Structure - Changting Chu; Lin Zhou; Yong Cheng; Xuxu Wang; Limin Chang; Ping Nie; Chunli Wang; Limin Wang (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Dual-emissive europium doped UiO-66-based ratiometric light-up biosensor for highly sensitive detection of histidinemia biomarker - Li Li; Lin-Lin Zhang; Jin Zou; Jiamin Zou; Lu-Ying Duan; Yansha Gao; Guanwei Peng; Xigen Huang; Limin Lu (Analytica Chimica Acta, 2024)

Regulating defect density of iron based metal–organic frameworks by defective ligands functionalization to enhance fenton-like activity and stability - Limin Duan; Huihao Jiang; Borui Cai; Wenhao Wu; Daohui Lin; Kun Yang (Chemical Engineering Journal, 2024)

Lower Cretaceous volcanic-sedimentary successions of the continental rift basin in the Songliao Basin, northeast China: Implication in high-quality reservoir prediction and hydrocarbon potential - Cong Hu; Qingjie Deng; Lin Lin; Mingyi Hu; Xinyu Hou; Limin Zong; Peng Song; Oumar Ibrahima Kane; Quansheng Cai; Zhonggui Hu (Marine and Petroleum Geology, 2023)

Sources of polychlorinated biphenyls (PCBs) in sediments of the East China marginal seas: Role of unintentionally-produced PCBs - Huimin Yu; Tian Lin; Limin Hu; Gerhard Lammel; Shizhen Zhao; Xueshi Sun; Xiao Wu; Zhigang Guo (Environmental Pollution, 2023)

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Transfer learning improves landslide susceptibility assessment - Haojie Wang; Lin Wang; Limin Zhang (Gondwana Research, 2023)

Machine learning powered high-resolution co-seismic landslide detection - Haojie Wang; Limin Zhang; Lin Wang; Ruilin Fan; Shengyang Zhou; Yejia Qiang; Ming Peng (Gondwana Research, 2023)

Physiologically based pharmacokinetic model combined with reverse dose method to study the nephrotoxic tolerance dose of tacrolimus - Limin Cai; Meng Ke; Han Wang; Wanhong Wu; Rongfang Lin; Pinfang Huang; Cuihong Lin (Archives of Toxicology, 2023)

How does Microcystis aeruginosa respond to elevated temperature? - Yongqi Guo; Han Meng; Sichuan Zhao; Zixuan Wang; Lin Zhu; Dailan Deng; Jine Liu; Huan He; Wenming Xie; Guoxiang Wang; Limin Zhang (Science of The Total Environment, 2023)

Microbiome assembly mechanism and functional potential in enhanced biological phosphorus removal system enriched with Tetrasphaera-related polyphosphate accumulating organisms - Hui Wang; Limin Lin; Lu Zhang; Ping Han; Feng Ju (Environmental Research, 2023)

Ultralow loaded waste polystyrene derived hyper-cross-linked polymer for incineration flue gas demercuration: Synergistic effect of transition metal and halogen species - Yifan Xu; Limin Liu; Yueqing Xu; Xiaofei Yan; Cheng Zhang; Zifei Sun; Xiaochen Lin; Yufeng Duan; Houhu Zhang (Chemical Engineering Journal, 2023)

Multimode damping optimization of a long-span suspension bridge with damped outriggers for suppressing vortex-induced vibrations - Zhanhang Liu; Lin Chen; Limin Sun; Lin Zhao; Wei Cui; Hua Guan (Engineering Structures, 2023)

Extraction and separation of Li+ from high-ratio Mg/Li salt lake brines by [C2mim][NTf2] ionic liquid and a homemade extractor - Jiawei Lu; Limin Jiao; Jialiang Chen; Yilin Zhang; Qiqi Guo; Yu Yang; Mingzhang Lin (Desalination, 2023)

Full-scale experimental study on dynamic behaviors of a three-cable network with a pretensioned cross-tie - Lin Chen; Lei Qin; Fangdian Di; Limin Sun; Yiqing Zou; Zhiquan Huang (Engineering Structures, 2023)

Defective iron based metal-organic frameworks derived from zero-valent iron for highly efficient fenton-like catalysis - Limin Duan; Huihao Jiang; Wenhao Wu; Daohui Lin; Kun Yang (Journal of Hazardous Materials, 2023)

Hydrogen bonding donor/acceptor active sites exposed on imide-functionalized carbon dots aid in enhancing arsenic adsorption performance - Ze Lin; Limin Jin; Yanbiao Liu; Ying Wang (Chemical Engineering Journal, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Convective-scale ensemble forecasts of the heavy precipitation of Typhoon Lekima (2019) in Zhejiang Province - Fanyu Xu; Huiling Yuan; Limin Lin; Wenbin Chen (Atmospheric Research, 2023)

MiR-29a-3p inhibits high-grade transformation and epithelial–mesenchymal transition of lacrimal gland adenoid cystic carcinoma by targeting Quaking - Fei Xu; Meixia Jiang; Qin Tang; Jiaqi Lin; Xun Liu; Chuanli Zhang; Jinzhi Zhao; Yanjin He; Lijie Dong; Limin Zhu; Tingting Lin (Molecular Biology Reports, 2023)

Molecular characterization of humic-like substances (HULIS) in atmospheric particles (PM2.5) in offshore Eastern China Sea (OECS) using solid-phase extraction coupled with ESI FT-ICR MS - Hao Sun; Zilan Wu; Xinyuan Kang; Chao Zhu; Limin Yu; Ru Li; Zhongsheng Lin; Jianmin Chen (Atmospheric Environment, 2023)

SERS detection of thiram using polyacrylamide hydrogel-enclosed gold nanoparticle aggregates - Kaiqiang Wang; Zilin Yue; Xiu Fang; Hong Lin; Lei Wang; Limin Cao; Jianxin Sui; Lei Ju (Science of The Total Environment, 2023)

Combination of highly photovoltaic and highly transparent materials enables record performance semitransparent organic solar cells - Lin Zhao; Xuexiang Huang; Yukai Wang; Sang Young Jeong; Bin Huang; Jiawei Deng; Jiabin Liu; Yujun Cheng; Han Young Woo; Feiyan Wu; Limin Chen; Lie Chen (Chemical Engineering Journal, 2023)

Isolation and identification of new source of bacteriocin-producing Lactobacillus plantarum C010 and growth kinetics of its batch fermentation - Jinyue Dai; Limin Fang; Manmin Zhang; Huaili Deng; Xin Cheng; Mingyin Yao; Lin Huang (World Journal of Microbiology and Biotechnology, 2022)

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Petrogenesis, geochemistry and geological significance of Paleocene Granite in South Gangdese, Tibet - Chengzhi Li; Wenguang Yang; Lidong Zhu; Zhen Yang; Limin Lin; Xin Su; Hongliang Zhang (Acta Geochimica, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Dissolution Testing in Drug Product Development: Workshop Summary Report - Andreas Abend; David Curran; Jesse Kuiper; Xujin Lu; Hanlin Li; Andre Hermans; Pramod Kotwal; Dorys A. Diaz; Michael J. Cohen; Limin Zhang; Erika Stippler; German Drazer; et al. (The AAPS Journal, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Mobile carbon supply in trees and shrubs at the alpine treeline ecotone - Qing-Wei Wang; Cheng-Gang Liu; Wangming Zhou; Lin Qi; Li Zhou; Dapao Yu; Limin Dai (Plant Ecology, 2018)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Statistical analysis of the relationship between climate-induced maize yield and rainy-season precipitation across Inner Mongolia, North China - Jin Huang; Xin Chen; Limin Zhou; Yan Xue; Jie Lin (Theoretical and Applied Climatology, 2017)

No-tillage effects on N and P exports across a rice-planted watershed - Xinqiang Liang; Zhibo Wang; Yixiang Zhang; Chunyan Zhu; Limin Lin; Lixian Xu (Environmental Science and Pollution Research, 2016)

Carbon stock of larch plantations and its comparison with an old-growth forest in northeast China - Guang Qi; Hua Chen; Li Zhou; Xinchuang Wang; Wangming Zhou; Lin Qi; Yuhua Yang; Fengling Yang; Qingli Wang; Limin Dai (Chinese Geographical Science, 2016)

Formation mechanisms of the alpine Erman’s birch (Betula ermanii) treeline on Changbai Mountain in Northeast China - Dapao Yu; Qingwei Wang; Jiaqing Liu; Wangming Zhou; Lin Qi; Xiaoyu Wang; Li Zhou; Limin Dai (Trees, 2014)

Comparison of Intestinal Absorption and Disposition of Structurally Similar Bioactive Flavones in Radix Scutellariae - Chenrui Li; Li Zhang; Limin Zhou; Siu Kwan Wo; Ge Lin; Zhong Zuo (The AAPS Journal, 2012)

Major Forest Types and the Evolution of Sustainable Forestry in China - Limin Dai; Yue Wang; Dongkai Su; Li Zhou; Dapao Yu; Bernard J. Lewis; Lin Qi (Environmental Management, 2011)

Erratum to: Quantification of land use/land cover changes in Pearl River Delta and its impact on regional climate in summer using numerical modeling - Wenshi Lin; Lu Zhang; Dongsheng Du; Limin Yang; Hui Lin; Yuanzhi Zhang; Jiangnan Li (Regional Environmental Change, 2011)

Synergistic use of optical and InSAR data for urban impervious surface mapping: a case study in Hong Kong - Liming Jiang; Mingsheng Liao; Hui Lin; Limin Yang (International Journal of Remote Sensing, 2009)

Quantification of land use/land cover changes in Pearl River Delta and its impact on regional climate in summer using numerical modeling - Wenshi Lin; Lu Zhang; Dongsheng Du; Limin Yang; Hui Lin; Yuanzhi Zhang; Jiangnan Li (Regional Environmental Change, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Habitat selection and the change in distribution of asian elephants in Mengyang Protected Area, Yunnan, China - Liu Lin; Limin Feng; Wenjing Pan; Xianming Guo; Jianwei Zhao; Aidong Luo; Li Zhang (Mammal Research, 2008)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Influence of ultrasonic treatment on the allergenic properties of Shrimp (Penaeus vannamei) Allergen - Li Zhenxing; Lin Hong; Cao Limin (Journal of Ocean University of China, 2006)

Anti-enrofloxacin antibody production by using enrofloxacin-screened HSA as an immunogen - Chune Liu; Hong Lin; Limin Cao; Jie Jiang (Journal of Ocean University of China, 2005)